Human papilloma virus and its association with preneoplastic and neoplastic lesions of the cervix - Herrera, Gustavo (2015)
Intraephitelial lesions and invasive cancer of the uterine cervix are associated with human papilloma virus infection. For its detection, cytology, colposcopy and directed biopsies should be perfomed. Between february 1994 and september 1995, 438 patients were evaluated in the Teaching Departament of San Agustin University and Honorio Delgado Hospital. In 73 patients (16,66%) colposcopy was positive and a directed biopsy was performed. In 66 of these patients (90,41%), the histologically findings were: 20 (30,30%) low grade squamous intraepithelial lesions; 35 (53,03%) high grade lesions and in 11 patients (16,66%) invasive cancer. Sexual relations before 18 years, more than 3 sexual partners and the antecedent of sexual transmitted infections were risk factors; but cigarette smoking, low social status and the use of contraceptive methods, were not. In 22 patients (33,33%) histologically changes produced by H.P.V. infection were found and 12 patients (18,18%) had positive vulvar biopsy for H.P.V. In 27 patients the cytologic smear was negative. False negative cytology in this study was 40,90%.